1989
DOI: 10.1016/0304-3959(89)90079-1
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent pain and mechanical hyperalgesia in humans after intradermal injection of capsaicin

Abstract: Psychophysical measurements of pain and mechanical hyperalgesia were obtained following different doses of capsaicin injected intradermally into the forearms of human subjects. Each subject received a 10 microliter injection of the vehicle and capsaicin doses of 0.01, 0.1, 1, 10 and 100 micrograms. The relationship between capsaicin dose and the magnitude and duration of pain was determined using the method of magnitude estimation. In addition to pain, capsaicin produced a flare and mechanical hyperalgesia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
289
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(306 citation statements)
references
References 14 publications
15
289
1
1
Order By: Relevance
“…The data indicated that acute inflammation with IS resulted in a decrease in the PWL and PWT in the behavioral studies and this is consistent with previous studies using acute inflammatory mediators (Taiwo et al, 1987;Taiwo et al, 1989;Simone et al, 1989b;Gilchrist et al, 1996). Sensitization to heat was confirmed at the single fiber level, with CMH units showing a decrease in threshold and an increase in discharge rate in response to IS.…”
Section: Differences In Mechanisms Underlying Thermal Vs Mechanical Ssupporting
confidence: 90%
“…The data indicated that acute inflammation with IS resulted in a decrease in the PWL and PWT in the behavioral studies and this is consistent with previous studies using acute inflammatory mediators (Taiwo et al, 1987;Taiwo et al, 1989;Simone et al, 1989b;Gilchrist et al, 1996). Sensitization to heat was confirmed at the single fiber level, with CMH units showing a decrease in threshold and an increase in discharge rate in response to IS.…”
Section: Differences In Mechanisms Underlying Thermal Vs Mechanical Ssupporting
confidence: 90%
“…If we applied stimulus intensities of ϳ80 mA (20), most of these mechanoinsensitive fibers would be excited (23). In this case, the flare would become at least as large as after application of capsaicin (24). However, such high stimuli intensities cannot be used for routine clinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Intradermal injection of capsaicin, a main ingredient from hot chili peppers, elicits a strong acute pain accompanied by a multitude of sensory abnormalities including hyperalgesia (more pain to noxious stimuli) and allodynia [233,234] . Hence, Iadarola et al [235] designed experiments to image regional brain activity in normal volunteers during capsaicin-induced intense pain and mechanical allodynia by using the PET H 2 15 O-bolus method.…”
Section: Abnormal Pain Processing In the Hfmentioning
confidence: 99%